2014
DOI: 10.1002/psp.1853
|View full text |Cite
|
Sign up to set email alerts
|

A ‘Recipe for Depopulation’? School Closures and Local Population Decline in Saxony

Abstract: A popular notion asserts that closing the last primary school marks a community's demographic death. No young parents will remain, much less new ones move in. This notion is frequently voiced but rarely verified. Are school closures a cause or consequence of local decline? This study reviews existing research on school locations and peripheral population decline to show that expectations of a dramatic impact of school closures on out-migration are theoretically ill-founded. I proceed to discuss specific method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 49 publications
1
23
0
1
Order By: Relevance
“…We would expect to find that families with children are more likely to move to villages that have a primary school. Thus far, however, research has shown that the effect of the presence of a primary school on moving is limited (Amcoff 2012, Barakat 2015, Elshof 2015b).…”
Section: Other Amenities and Flows Of Moversmentioning
confidence: 99%
“…We would expect to find that families with children are more likely to move to villages that have a primary school. Thus far, however, research has shown that the effect of the presence of a primary school on moving is limited (Amcoff 2012, Barakat 2015, Elshof 2015b).…”
Section: Other Amenities and Flows Of Moversmentioning
confidence: 99%
“…(Barakat, ; Charles‐Edwards & Bell, ; Christopher & Leslie, ; Hochstenbach, Musterd, & Teernstra, ; Wesolowski, )…”
Section: Assemblage Thinking and Population Geographyunclassified
“…In Sweden, Amcoff () could not demonstrate evidence that school closure had an effect on the inward and outward flows of families with children, but pointed out that the well‐developed school bus system in rural Sweden could be an explanation for this lack of an effect. A study in Saxony, Germany by Barakat () also produced little evidence that either primary school closure, or the mere absence of a primary school in a municipality had a noteworthy effect on inward and outward flows. In this case, however, the period of observation was preceded by a period in which small schools were closed in favour of larger schools in key settlements, a situation to which the parents and children already had adapted their daily routines (Fickermann et al .…”
Section: Primary Schools and Moving Behaviourmentioning
confidence: 99%
“…Among local policy‐makers and inhabitants of rural villages, a persistent image exists that villages without a primary school are not an attractive place of residence for families with children, and that school closures therefore are a ‘recipe for depopulation’ (Barakat ). Primary schools are perceived as symbols of healthy, viable and prosperous communities (Egelund & Laustsen ; Woods ; Haartsen & Van Wissen ).…”
Section: Introductionmentioning
confidence: 99%